2011
DOI: 10.1186/cc10265
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and physical recovery after a critical illness: a multi-centre randomised controlled trial of a home-based physical rehabilitation program

Abstract: IntroductionSignificant physical sequelae exist for some survivors of a critical illness. There are, however, few studies that have examined specific interventions to improve their recovery, and none have tested a home-based physical rehabilitation program incorporating trainer visits to participants' homes. This study was designed to test the effect of an individualised eight-week home-based physical rehabilitation program on recovery.MethodsA multi-centre randomised controlled trial design was used. Adult in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
244
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(256 citation statements)
references
References 48 publications
4
244
2
6
Order By: Relevance
“…According to a study conducted by Elliott et al 18 , the patients of the intervention group who received early mobilization traveled a greater distance in the 6MWT in all the assessments conducted in comparison with the control group. In general, participants of the intervention group improved the distance of the 6MWT in 27% at 8 weeks and 39% at 26 weeks of the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study conducted by Elliott et al 18 , the patients of the intervention group who received early mobilization traveled a greater distance in the 6MWT in all the assessments conducted in comparison with the control group. In general, participants of the intervention group improved the distance of the 6MWT in 27% at 8 weeks and 39% at 26 weeks of the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A mediana do tempo de internação na UTI foi de 5 (3)(4)(5)(6)(7)(8)(9) dias, e de internação hospitalar de 13 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Original Researchunclassified
See 1 more Smart Citation
“…At 12 months, there remained a significant proportion of patients experiencing symptoms at the most severe end of each symptom scale (table 1) Previous investigators have shown that HRQoL is reduced following critical illness and that spontaneous improvement is limited, sometimes over many years (1). Some (but not all) rehabilitation trials have demonstrated improved functional outcomes, but have not necessarily improved HRQoL (4,5). In this analysis, we have shown that symptoms that influence daily life are prevalent following ICU discharge, are highly correlated with HRQoL, and frequently worsen in their severity over time.…”
mentioning
confidence: 99%
“…Patients who survive critical illness sometimes report poor health-related quality of life (HRQoL) (1), but rehabilitation trials have mostly found no effect on this and other measures of health status (2)(3)(4)(5). Most critical care research has employed tools such as the Medical Outcomes Study Short Form questionnaires (SF12/SF36) or EuroQol (EQ-5D) to measure HRQoL.…”
mentioning
confidence: 99%